The Role of the Built Environment in Human Life. Selected Issues - Lamprecht, Mariusz (European Spatial Research and Policy, 2017)
Creation of the built environment and research in this field pose a particularly difficult challenge nowadays. The pace of social and technological change does not allow for evolutionary development of cities and the formation of their land use according to current conditions. Creating spatial solutions that are unmatched in their contexts is becoming not only possible, but very probable (see Alexander, 1964). The development of the built environment involves not only art, technology, history, economics and law, but also philosophy, culture, medicine, psychology, sociology and many other spheres in which human life is manifested. However, only a relatively small number of disciplines such as spatial planning, urban design, urban planning, etc. (ignoring at this point the differences in the meaning of the concepts) in their application layer are meant to create space and bear responsibility for it. Also society has certain requirements of practical nature towards them. This article attempts to outline the nature of research on space urbanised by people and to determine the four main fields of research aimed at the problems of man and the built environment. In the next part, particular attention is paid to issues related to the impact of the built environment on the life of its residents in order to highlight the particular role and complexity of this area of research. This study, acting as a kind of test of the research, cannot be considered representative. Nevertheless, the analysis prompts several reflections on the current and future role of the built environment in the development of our civilisation, as well as further challenges related to it.